2011
DOI: 10.1051/0004-6361/201116927
|View full text |Cite
|
Sign up to set email alerts
|

X Herculis and TX Piscium: two cases of ISM interaction with stellar winds observed byHerschel

Abstract: The asymptotic giant branch (AGB) stars X Her and TX Psc have been imaged at 70 and 160 μm with the PACS instrument onboard the Herschel satellite, as part of the large MESS (Mass loss of Evolved StarS) guaranteed time key program. The images reveal an axisymmetric extended structure with its axis oriented along the space motion of the stars. This extended structure is very likely to be shaped by the interaction of the wind ejected by the AGB star with the surrounding interstellar medium (ISM). As predicted by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 79 publications
6
41
0
Order By: Relevance
“…A deviation from spherical symmetry for the circumstellar environment of TX Psc was detected by several authors at different spatial scales and wavelengths (e.g. Cruzalèbes et al 1998;Ragland et al 2006;Sacuto et al 2011b;Jorissen et al 2011;Hron et al, in prep.). Clearly, the circumstellar environment of TX Psc is very complex, and most likely unrelated effects shape the morphology in different regions, resulting in a wide variety of structures.…”
Section: Approach 1: Geometric Modelsmentioning
confidence: 85%
See 1 more Smart Citation
“…A deviation from spherical symmetry for the circumstellar environment of TX Psc was detected by several authors at different spatial scales and wavelengths (e.g. Cruzalèbes et al 1998;Ragland et al 2006;Sacuto et al 2011b;Jorissen et al 2011;Hron et al, in prep.). Clearly, the circumstellar environment of TX Psc is very complex, and most likely unrelated effects shape the morphology in different regions, resulting in a wide variety of structures.…”
Section: Approach 1: Geometric Modelsmentioning
confidence: 85%
“…TX Psc is one of the brightest and closest carbon-rich AGB stars. It is listed as an irregular variable in the General Catalogue of Variable stars (Samus et al 2009) with a mean brightness of ∼5 mag and a peak-to-peak amplitude of 0.4 mag in the V-band (Jorissen et al 2011). Distance estimates range from 275 to 315 pc (van Leeuwen 2007;Claussen et al 1987;Bergeat & Chevallier 2005).…”
Section: Introductionmentioning
confidence: 99%
“…An overview of the MESS objects is given by Cox et al (2012) and detailed studies of individual objects are presented in Ladjal et al (2010a), Kerschbaum et al (2010), Jorissen et al (2011, 2013, Decin et al (2011Decin et al ( , 2012, van Hoof et al (2013), and Mečina et al (2014 Sacuto et al (2008) and Paladini et al (in prep.). The MIDI observations do not deviate from spherical symmetry.…”
Section: Herschel/pacsmentioning
confidence: 99%
“…Ueta et al (2006), Jorissen et al (2011), andCox et al (2012) showed that fast-moving AGB stars can alter the wind bubble and produce a bow shock in the direction of the space motion at the interface of the wind and the ISM. For stars with a low space velocity, the CSE appears elliptical (Weaver et al 1977).…”
Section: Origin Of the Elliptical Emissionmentioning
confidence: 99%
“…The resulting fluxes are F ν,12 = 0.207 Jy and F ν,22 = 1.650 Jy at 12 μm and 22 μm, respectively. Adopting the corresponding absorption coefficients of astronomical silicates Q abs,12 = 5.60 × 10 −2 and Q abs,22 = 3.39 × 10 −2 (Draine 1985), the 12 μm and 22 μm fluxes correspond to a temperature of 124 K (for details see Jorissen et al 2011).…”
Section: Dramentioning
confidence: 99%